2016
DOI: 10.1073/pnas.1524777113
|View full text |Cite
|
Sign up to set email alerts
|

Conformational dynamics of a membrane protein chaperone enables spatially regulated substrate capture and release

Abstract: Membrane protein biogenesis poses enormous challenges to cellular protein homeostasis and requires effective molecular chaperones. Compared with chaperones that promote soluble protein folding, membrane protein chaperones require tight spatiotemporal coordination of their substrate binding and release cycles. Here we define the chaperone cycle for cpSRP43, which protects the largest family of membrane proteins, the light harvesting chlorophyll a/b-binding proteins (LHCPs), during their delivery. Biochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(103 citation statements)
references
References 47 publications
4
96
0
Order By: Relevance
“…Interestingly, levels of LHC proteins were clearly higher in ffc than in chaos, chaos/ffc, and cpftsy (Fig. 1C), indicating that cpSRP43 functions predominantly and independently from cpSRP54 in targeting of LHC proteins to the thylakoid membranes (Tzvetkova-Chevolleau et al, 2007;Liang et al, 2016). In summary, our initial results suggest that malfunction of the cpSRP pathway depresses steady-state levels of both LHCI and LHCII, while strongly reduced Chl b biosynthesis preferentially affects LHCII.…”
Section: Reduced Contents Of Lhcs In Ch1-2 and Cpsrp Mutantsmentioning
confidence: 71%
“…Interestingly, levels of LHC proteins were clearly higher in ffc than in chaos, chaos/ffc, and cpftsy (Fig. 1C), indicating that cpSRP43 functions predominantly and independently from cpSRP54 in targeting of LHC proteins to the thylakoid membranes (Tzvetkova-Chevolleau et al, 2007;Liang et al, 2016). In summary, our initial results suggest that malfunction of the cpSRP pathway depresses steady-state levels of both LHCI and LHCII, while strongly reduced Chl b biosynthesis preferentially affects LHCII.…”
Section: Reduced Contents Of Lhcs In Ch1-2 and Cpsrp Mutantsmentioning
confidence: 71%
“…cpSRP43 con-tains a substrate binding domain that recognizes LHCPs and two chromodomains, CD2 and CD3 (32,33). CD2 binds the C-terminal tail of the cpSRP54 M-domain to form the cpSRP, and CD3 provides an interaction site with the Alb3 translocase (see below) (34,35).…”
mentioning
confidence: 99%
“…The dynamic opening of the Get3•TA complex is unexpected, as crystallographic analyses suggested that in open Get3, the hydrophobic groove for TMD binding becomes discontiguous (7,26). Intriguingly, our recent (12) and current measurements showed that Get3•TA complexes exhibit high kinetic stability: Using a membrane protein chaperone, cpSRP43 (27,28), as an inert TA trap, the timescale for spontaneous dissociation of Bos1 from Get3 was measured to be ∼4 h (Fig. S4B).…”
Section: -H)mentioning
confidence: 82%
“…Plasmids for recombinant expression of Get3, Get4/5, Get1CD, and a superactive mutant of the cpSRP43 chaperone (intein-cpSRP43) and for in vitro translation of 3xStrep-SUMOnc-Bos1-opsin have been described (10,12,14,28). DNA encoding 2xStrep-Sbh1 was in the pACYCDuet-1 vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation